2020
DOI: 10.3390/polym12081642
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterisation of Acrylic Resin-Al Powder Composites Suitable for Additive Manufacturing

Abstract: Stereolithography is an additive manufacturing technology commonly used to build either prototypes or final parts. Nevertheless, the manufacture of structural parts has been ruled out owing to the poor mechanical properties of conventional UV-curable resins. Moreover, the inventory of available commercial resins is still limited and they exhibit low thermal and electrical conductivity values. In this work, some composite materials were designed using Al microparticles dispersed within an SLA commercial resin m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…On the other hand, three different types of resins manufactured by SL have been measured, obtaining similar values among them, and similar to those reported in the literature shown in this article. The highest thermal conductivity value is obtained for the standard resin, which is 0.366 ± 0.056 W/m K. As expected, this thermal conductivity value is lower than the values of the resins thermally doped with nanoparticles, conductivities around 0.600 W/m K for the resins [4], and 0.24 W/m K for the Aladditivated filaments [5].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…On the other hand, three different types of resins manufactured by SL have been measured, obtaining similar values among them, and similar to those reported in the literature shown in this article. The highest thermal conductivity value is obtained for the standard resin, which is 0.366 ± 0.056 W/m K. As expected, this thermal conductivity value is lower than the values of the resins thermally doped with nanoparticles, conductivities around 0.600 W/m K for the resins [4], and 0.24 W/m K for the Aladditivated filaments [5].…”
Section: Discussionsupporting
confidence: 61%
“…Nonetheless, it should be taken into account that these are studies in which nanofibers have been introduced into the materials to increase their thermal conductivity and it is logical that this value extracted from the literature corresponds to an addition of 3% Cu in the composition of the resin. Furthermore, the resins thermal conductivity is similar but higher than commercial additivated filaments ones with 25% Al additives, which is of 0.24 W/m K, as published in the article by Melchels et al [5].…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Light-curable resins are usually modified by incorporating nano-powders or their solution with specific desired properties as fillers, along with dispersants that ensure the uniform distribution of these fillers. , The active precursors required in our study can also be obtained by dispersing active seeds into any photocurable resin whose sensitive wavelength is 405 nm (Supporting Information Figure S3). But the stability of modified resins prepared in such a manner is low because the filler tends to eventually settle (after 1–2 days) such that the material becomes inhomogeneous.…”
Section: Methodsmentioning
confidence: 99%
“…Immense progression has been observed in the technology of photocuring resins over other conventional resin curing systems. Single-component formulation, a fast curing rate, environment friendliness, and time and energy efficiency are some of the befitting advantages provided by the photocuring resin technology. Studies are reported using nanofiller reinforcement such as silicon dioxide, graphene oxide, alumina, titanium carbide, and carbon black in photocuring resins for additive manufacturing. Experiments are demonstrated based on the reinforcement of natural and synthetic fibers in photocuring resins to create 3D-printed fiber-reinforced composites . There are numerous advantages in terms of strength, thermal stability, chemical resistance, abrasion, etc.…”
Section: Introductionmentioning
confidence: 99%